Information needs and sources used by small-scale horticulture farmers in Morogoro urban, Tanzania - Masele, Juma James (University of Dar es Salaam Library Journal, 2024)
While the role of information in improving small-scale horticultural farming in urban areas is widely acknowledged in the literature, its potential cannot be realized unless the information needs that enlighten the stakeholders about the appropriate information sources are known. This is because horticultural farming is an information intensive endeavour and it is full of uncertainties. This study investigated information needs and the sources used by small-scale horticulture farmers in Morogoro Urban in Tanzania. A mixed-method research design was used to collect data from 133 respondents. Questionnaires, observation, and interviews were used in the data collection process. Descriptive analysis was used inanalysing quantitative data, while content analysis was used for qualitative data. The findings of the study show that farmers needed information on sowing/harvesting time, disease and pest control, erosion control, harvest storage, and produce markets. Friends/colleagues ranked as important information sources, followed by extension officers, libraries, Internet, colleagues, cooperatives, Nanenane exhibitions, radio, and newspapers. The challenges faced including the unavailability of extension officers, and long distances to/from libraries were mentioned as significant factors hindering farmers ' use of small-scale horticultural farming information and horticultural development in general. Recommendations have been provided that, equip small-scale horticultural crop farmers with up-to-date knowledge and skills to shape the farmers' thinking, knowledge, and attitude. Such awareness will add value to the information exchanged through interpersonal relationships. Employing more skilled extension officers and the use of modern ICT to improve horticulture farmers ' information access is also recommended.